The Role of the Presbyter: an Investigation into the Adversus Haereses of Saint Irenaeus - Sobosan, Jeffrey G. (Scottish journal of theology, 1974)
Irenaeus constantly spoke of the presbyters who possess the succession from the Apostles; those who, together with the succession of the Episcopate, have received the certain gift of truth. For him the importance of the presbyter was based on apostolic succession: the presbyter was a teacher, and teaching determines faith; it is the means by which the faith is preserved and transmitted. The presbyter is a link in the long line of tradition; tradition which disciplines the faithful and determines the future of the church. For this reason alone the presbyter is important for Irenaeus. And this is the basis for the distinct way in which Irenaeus treats him. The presbyter is the primary minister, yet not necessarily a bishop. He is a leader of the Christian community assigned the task of preserving the faith, teaching it and making sure to defend it against error. He holds the chief seat in the administration of the Christian community, and is always associated with the episcopos or bishop. In the writings of Irenaeus there is no clear distinction made between these two terms.We must keep in mind that Christianity began as a movement, not as an established system or institution. The early Christians were all Jews and the authorised Jewish minister was the rabbi (presbyter). From the very beginning the apostles founded new communities and directed them. After particular communities were founded a need arose to select local leaders or administrators for each of these communities. We know from the New Testament that in the various local communities different names were given to these men: in Rome they were called presidents, in Corinth they were called governors, in Ephesus the name given to them was shepherds and in Phillipi they were known as caretakers and ministers. It is only in the Pastoral Epistles and in the Acts of the Apostles that we find these administrators called presbyters, episcopoi. Irenaeus adds further information to the development to the Christian hierarchy by expressing his views on the presbyter as servant of the community. In short the role or task of the presbyter was one of service to the Christian community.